Morpho-anatomical aterations in leaves of Fagus sylvatica L. and Quercus ilex L. in different environmental stress condition - Grossoni, P; Bussotti, F; Tani, C; Gravano, E (Chemosphere, 1998)
By means of anatomical and foliar structure observations, this paper examines the ecological behaviour of two different species of broadleaf (a mesophile one, beech, and a xerophile one, holm-oak), under different conditions of water supply. The purpose of this study was to evaluate their response in relation to possible climate changes. The results highlight certain similarities of behaviour (reduction of leaf surface, increased leaf thickness, increase of mechanical structures in xeric stands). The main difference between the two species lies in the tannins content, which increase in the epidermal cells (vacuoles and walls) only in beech trees in xeric conditions
Keywords: Fagus sylvatica; foliar structure; Quercus ilex; xeric conditions (voyant)